Case Report: Exceptional Response to Poziotinib in Patient with Metastatic Non-Small Cell Lung Cancer With EGFR Exon 20 Insertion Mutation - Prelaj, Arsela; Bottiglieri, Achille; Bhat, Gajanan; Washington, Rocky; Calareso, Giuseppina; Greco, Gabriella Francesca; Ferrara, Roberto; Brambilla, Marta; De Toma, Alessandro; Occhipinti, Mario; Manglaviti, Sara; Soro, Alberto; et al. (Frontiers in Oncology, 2022)
Amongst the several next-generation tyrosine kinase inhibitors (TKIs) tested against uncommon EFGR alterations, poziotinib demonstrated to be a powerful agent for metastatic non-small-cell lung cancer (mNSCLC) with aberrations in EFGR and HER2 exon 20. Herein, we report the first published case of a patient affected mNSCLC harboring an EGFR exon 20 insertion mutation who achieved a complete response (CR) under treatment with poziotinib, as part of the ZENITH20 trial. In January 2021, a former smoker 62-year-old female patient was diagnosed with relapse after two surgeries and post-operative chemotherapy of mNSCLC at liver and retroperitoneal nodes: given the identification by Next Generation Sequencing (NGS) of EGFR exon 20 mutation, she was enrolled in ZENITH20-cohort 5 trial, a phase 2 multicentre study aimed to assess the efficacy and safety of poziotinib in patients with EGFR or HER2 exon 20 insertion mutations. Poziotinib as first-line systemic therapy for metastatic disease was initiated at the end of January 2021 and administrated at the initial dosage of 8 mg orally twice daily (BID). The most common side effects onset since the very beginning of the treatment included alopecia, macular skin rash, diarrhea, xerostomia, and conjunctivitis. As a consequence of the adverse events, poziotinib was discontinuously assumed and then reduced at 6 mg orally BID on April 2021. After the dose de-escalation, the adverse events improved, and the patient better tolerated the treatment without further interruption. Since the first revaluation (after 4 weeks of therapy), the treatment with poziotinib resulted to be remarkably effective, with a partial response (PR) subsequently confirmed in May and July 2021. Then, in October 2021, CT scan confirmed a CR, maintained with good tolerance at the last revaluation in February 2022. In this case, poziotinib has represented a successful and well tolerated alternative compared to chemotherapy.